Exploring the Effect of Esomeprazole on Gastric and Duodenal Fluid Volumes and Absorption of Ritonavir - Tom de Waal; Jari Rubbens; Michael Grimm; Vincent Vandecaveye; Jan Tack; Werner Weitschies; Joachim Brouwers; Patrick Augustijns (Pharmaceutics, 2020)
Proton-pump inhibitors (PPIs), frequently prescribed to lower gastric acid secretion, often exert an effect on the absorption of co-medicated drug products. A previous study showed decreased plasma levels of the lipophilic drug ritonavir after co-administration with the PPI Nexium (40 mg esomeprazole), even though duodenal concentrations were not affected. The present study explored if a PPI-induced decrease in gastrointestinal (GI) fluid volume might contribute to the reduced absorption of ritonavir. In an exploratory cross-over study, five volunteers were given a Norvir tablet (100 mg ritonavir) orally, once without PPI pre-treatment and once after a three-day pre-treatment with the PPI esomeprazole. Blood samples were collected for eight hours to assess ritonavir absorption and magnetic resonance imaging (MRI) was used to determine the gastric and duodenal fluid volumes during the first three hours after administration of the tablet. The results confirmed that PPI intake reduced ritonavir plasma concentrations by 40%. The gastric residual volume and gastric fluid volume decreased by 41% and 44% respectively, while the duodenal fluid volume was reduced by 33%. These data suggest that the PPI esomeprazole lowers the available fluid volume for dissolution, which may limit the amount of ritonavir that can be absorbed. Although additional factors may play a role, the effect of PPI intake on the GI fluid volume should be considered when simulating the absorption of poorly soluble drugs like ritonavir in real-life conditions.